Effects of fuel composition at varying air-fuel ratio on knock resistance during spark-ignition combustion. (15th July 2023) - Almaleki, Ahmad; Hellier, Paul; Ladommatos, Nicos; Talibi, Midhat; Khan, Zuhaib
Highlights: Knock resistance of a test fuel depends on the air–fuel ratio at which the spark-ignition engine is operated and the chemical composition of the test fuel. Regardless of composition or RON number of test fuels, knocking combustion occurred at a lower engine CR at fuel rich conditions (λ < 1) relative to stoichiometric (λ = 1). The gasoline test fuels were less sensitive to changes in exhaust lambda λ than the purely paraffinic primary reference fuels, exhibiting less variation in the operating limit of engine CR at varying exhaust lambda λ. The influence of fuel composition was much reduced at fuel rich conditions relative to stoichiometric (λ = 1). The addition of ethanol to gasoline increases the rate of combustion and decreases peak-to-peak in-cylinder variation compared to PRFs and other gasoline fuels. Abstract: Knock resistance of liquid fuels for spark-ignition engines is determined using standardised tests (RON and MON), however, these measurements are not undertaken at the same air–fuel ratio for different fuels. In contrast, modern engines have a highly controlled air–fuel ratio, often operating in a very narrow range around stoichiometric in order to reduce pollutant emissions and achieve high thermal efficiencies. As global efforts to increase the utilisation of renewable fuels of varying composition intensify, understanding of the differing knock sensitivity to the air–fuel ratio at which the engine is operated provides a vital opportunity to further optimise combustion processes. This paper investigates the influence of varying relative air–fuel ratios, the exhaust λ, on the knock resistance of a range of fuels of varying RON values and chemical compositions. Binary component primary reference fuels and practical gasolines of equivalent RON values were tested with a Ricardo E6 variable compression engine operated at conditions similar to those used for RON tests. It was found that the engine compression ratio which could be utilised before a knock threshold was exceeded was the same for fuels of equivalent RON at fuel rich conditions but differed appreciably at stoichiometric conditions (λ = 1). The knock resistance of purely paraffinic reference fuels was observed to be more sensitive to changes in exhaust λ than the aromatic gasoline fuels, especially at λ = 1, where the former fuels required significantly higher engine compression ratios to achieve equivalent levels of knock.